Co(dmgH)2pyCl as a noble-metal-free co-catalyst for highly efficient photocatalytic hydrogen evolution over hexagonal ZnIn2S4. Issue 8 (14th January 2016) - Gao, Yanhong; Lin, Huaxiang; Zhang, Shiying; Li, Zhaohui
Abstract : Co(dmgH)2 pyCl is an efficient co-catalyst for photocatalytic hydrogen evolution and the activity over Co(dmgH)2 pyCl/ZnIn2 S4 is superior to that over Pt/ZnIn2 S4 . Abstract : Co(dmgH)2 pyCl/ZnIn2 S4 composites (dmgH = dimethylglyoxime and py = pyridine) with different amounts of Co(dmgH)2 pyCl loaded were prepared from hexagonal ZnIn2 S4 and Co(dmgH)2 pyCl via an impregnation method. The photocatalytic activity for hydrogen evolution over the as-prepared Co(dmgH)2 pyCl/ZnIn2 S4 composites under visible light irradiation was investigated. It was found that the hydrogen evolution over hexagonal ZnIn2 S4 can be significantly increased by loading Co(dmgH)2 pyCl as a co-catalyst. An optimum activity was achieved over 3.0 wt% Co(dmgH)2 pyCl/ZnIn2 S4 composite, with 1438.5 μmol hydrogen generated and a turnover number of 387 (based on Co(dmgH)2 pyCl) reached in 8 h visible light irradiation. This value is much higher than that obtained over Pt loaded ZnIn2 S4 under similar conditions, indicating that Co(dmgH)2 pyCl can be a highly efficient noble-metal-free co-catalyst for photocatalytic hydrogen evolution over hexagonal ZnIn2 S4 . The mechanism for the hydrogen evolution over the Co(dmgH)2 pyCl/ZnIn2 S4 composite was also proposed. This work paves a way to the development of highly efficient noble-metal-free photocatalytic systems for hydrogen evolution.